2016
DOI: 10.1177/1091581816655303
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of β-Caryophyllene Oil

Abstract: In a subchronic toxicity study, administration of β-caryophyllene (BCP) oil by oral gavage to Wistar rats at dosages of 0, 150, 450, or 700 mg/kg/d for 90 days, including a 21-day recovery period, did not produce any significant toxicologic manifestations. The study design also included a 28-day interim sacrifice in the control and high-dose groups. The BCP oil test article was well tolerated as evidenced by the absence of major treatment-related changes in the general condition and appearance of the rats, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…In rodents, overall absence of neurotoxicity at the dosages used to study pharmacological effects (20 to 100 mg/kg) has been found [10,41]. Moreover, in various studies, no damage to the gastric mucosa has been observed, nor changes in other internal organs (brain, heart, liver, lungs, spleen, kidneys) or in haematological parameters have been reported both in female Swiss mice and in Wistar rats [10,62]. Moreover, an Ames test has shown no mutagenicity [63].…”
Section: β-Caryophyllene Toxicitymentioning
confidence: 98%
See 2 more Smart Citations
“…In rodents, overall absence of neurotoxicity at the dosages used to study pharmacological effects (20 to 100 mg/kg) has been found [10,41]. Moreover, in various studies, no damage to the gastric mucosa has been observed, nor changes in other internal organs (brain, heart, liver, lungs, spleen, kidneys) or in haematological parameters have been reported both in female Swiss mice and in Wistar rats [10,62]. Moreover, an Ames test has shown no mutagenicity [63].…”
Section: β-Caryophyllene Toxicitymentioning
confidence: 98%
“…Studies about acute toxicity have been carried out. The oral administration of 2000 mg/kg of the molecule in female Swiss mice induces no toxic effects [10], whereas in rats an LD 50 greater than 5000 mg/kg has been calculated [62].…”
Section: β-Caryophyllene Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is an approved flavouring agent under the US Code of Federal Regulations and by the US Food and Drug Administration (FDA) . Recent studies on the toxicity (acute, repeated‐dose and subchronic) of β‐caryophyllene in rodents did not detect genotoxicity or any adverse clinical signs and concluded it to be safe with toxicity dose higher than 2000 mg/kg of the body weight . In case of the other major constituent, that is germacrene D, there is a lack in the information regarding its toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The GC-MS chromatogram along with the abundance and structures of majorly identified constituents of the essential oil from young leaves has been represented in Figure 3 and Table 1 40,41 Reproductive tissues including female and male inflorescence showed comparatively more complex profile of the essential oil ( Figure S5; Tables S4-S5 42 Recent studies on the toxicity (acute, repeated-dose and subchronic) of β-caryophyllene in rodents did not detect genotoxicity or any adverse clinical signs and concluded it to be safe with toxicity dose higher than 2000 mg/kg of the body weight. [43][44][45] In case of the other major constituent, that is germacrene D, there is a lack in the information regarding its toxicity. However, as per Maximum Daily Intake' (mTAMDI) and 'Threshold of Concern' values 3900 and 1800 μg/person/day, respectively.…”
Section: Essential Oil Profiling Of P Betleoidesmentioning
confidence: 99%